Variations of Endocrine Hormones Concentrations in Tupaia belangeri under Simulated Seasonal Acclimatized: Role of Leptin Sensitivity - Zhu, Wan-long; Mu, Yuan; Zhang, Lin; Wang, Zheng-kun (Journal of Stress Physiology & Biochemistry, 2013)
Seasonal variations in endocrine hormones concentrations are important for the survival of small mammals during acclimatization. In order to understand the role of leptin sensitivity on other endocrine hormones concentrations, we examined body mass, serum leptin level, serum insulin, tri-iodothyronine (T 3), thyroxine (T4) and thyroid stimulating hormone (TSH) concentrations in Tupaia belangeri under seasonal acclimatized (The simulated temperature and photoperiod in winter: 5°C and SD, 8h:16h Light:Dark; the simulated temperature and photoperiod in summer: 30°C and SD, 16h:8h Light:Dark) for 4 weeks. The results showed that body mass, serum leptin level, serum T3, T4 concentrations and T3/T4 showed significant variation, but serum insulin and TSH concentrations showed no variations between treatment group. There were positive correlation between serum leptin level and insulin, T4 concentrations, and were negative correlation between serum leptin level and body mass, T3 concentrations. However, no correlation was found between serum TSH concentrations and serum leptin level. The present results suggested T. belangeri overcome winter thermogenesis challenges by adjusting body mass and endocrine hormones concentrations. Furthermore, leptin may play an potential role in their body mass regulation in T. belangeri.